Organizational Influences and Performance Impact of Cross-Border E-Commerce Barriers: The Moderating Role of Home Country Digital Infrastructure and Foreign Market Internet Penetration - Eduardsen, Jonas; Marinova, Svetla; Leonidou, Leonidas C.; Christodoulides, Paul (My University, 2023)
Despite voluminous research on barriers to exporting, knowledge on the inhibiting role of specific obstacles confronted by firms when exporting via cross-border e-commerce (CBEC) is virtually absent. Using data from a cross-industry sample of 1256 firms located in 25 different European countries, we shed light on this issue by examining the organizational determinants and performance outcomes of CBEC barriers. The results revealed these barriers are more evident in the case of firms with smaller size, lacking experience, and having no affiliation with other companies. It was also found that all different types of CBEC barriers, namely financial complexities, coping with foreign markets, supplier restrictions, technical difficulties, and product limitations, are negatively affecting online export performance. Finally, both the home country’s level of digital infrastructure and the foreign market’s Internet penetration rate exhibited a strong moderating effect on the association between CBEC barriers and export performance.
Keywords: Cross-border e-commerce; Exporting; Export barriers; Export performance; E-commerce